A Prospective Study to Evaluate the Predictivity of Risk Malignancy Index in Adnexal Masses - Elmastas, Narin Yar; Obut, Mehmet; Tunc, Senem Yaman (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVE: To evaluate the efficiency of CA-125, menopausal status, ultrasound features and risk malignancy index in predicting malignancy in patients with an adnexal mass. STUDY DESIGN: This study was designed prospectively and 212 patients who applied to our hospital and met the study criteria were included. Preoperatively RMI value was calculated for the differentiation of benign from malignant patients. The diagnosis was confirmed by histopathology. Kolmogorov-Smirnov, Yates correction, Pearson Chi-Square and Student’s t-test were used for statistical analysis. ROC curves were drawn as diagnostic tests and the test results were presented. RESULTS: Of 212 patients included in our study, 174 (82%) patients’ were reported as benign, 6 (3%) borderline and 32 (15%) malignant. In predicting malignancy, the malignity risk index with 200 cutoff value the sensitivity and specivity was 87% and 80% respectively. However, when the cutoff value of malignity risk index taken as 112, the sensitivity was unchanged but the specificity increased to 90%. Similarly, when CA-125’s cutoff value was taken as 46U/mL, the sensitivity did not change but the specificity increased from 68% to 72%. CONCLUSION: Malignancy risk index is a method that has high sensitivity and specificity. Preoperative-op RMI calculation can provide accurate predictions for the establishment of an appropriate surgical plan for pelvic masses or referral to tertiary centers.